An experimental test of the role of structural blue and melanin-based chestnut coloration in aggressive contests in male eastern bluebirds - Mercadante, Austin; Hill, Geoffrey E. (Frontiers in Ecology and Evolution, 2014)
Male eastern bluebirds (Sialia sialis) have feathers with either structurally based blue coloration or melanin-based chestnut coloration, and they hold territories during the breeding season that they defend vigorously. We tested whether the melanin pigmentation or structural coloration of feathers serve as signals during intrasexual aggressive encounters by placing color-modified stuffed bluebirds in male territories. We recorded the time to attack and the intensity of attacks on each model, and we then compared the response to color-enhanced vs. color-reduced models. Male bluebirds attacked models with brighter and more chromatic blue coloration significantly more often than they attacked models with darker and less chromatic blue coloration. In contrast, the darkness of the chestnut breast coloration did not have a significant effect on the rate at which models were attacked. We conclude that territorial male bluebirds perceive intruding males with brighter blue coloration as a greater threat than males with drabber blue coloration, presumably because blue coloration is a signal of fighting ability. In contrast, the chestnut coloration of breast feathers appears to be a signal of gender and sexual maturity and not a graded signal of social status.